Boosting elementary science engagement: A qualitative study of baamboozle-based game learning in Indonesian classrooms - Alfiah, Alfiah; Sholihah, Mar'atus (Asatiza: Jurnal Pendidikan, 2025)
This study explores the implementation of Baamboozle-based Game-Based Learning (GBL) to enhance student engagement in science classes at Assunniyyah Kencong Elementary School. Adopting a qualitative case study approach, the research involved 25 third-grade students and science teachers over six weeks. Data were collected through participatory observation, in-depth interviews, and documentation. Findings reveal a marked improvement in student participation, including a 45% increase in verbal engagement, a 27–38% rise in discussion involvement, and stronger collaborative skills. The most notable progress occurred in initially low-participation classrooms (38% growth). Bamboozled facilitated a differentiated learning environment that accommodated diverse learning styles. Despite technical constraints, adaptive strategies ensured pedagogical effectiveness. Innovation fosters 21st-century skills and suggests potential for broader paradigm shifts in elementary education. This study underscores the value of GBL in promoting active learning while highlighting practical considerations for its implementation.